Pendampingan Pelaksanaan Pekerjaan Pondasi Beton Sumuran dengan Metode Pengeboran Semi-Mekanik Di Kelurahan Katonsari Kecamatan Demak Kabupaten Demak - Cahyono, Dhamang Budi; Widiatmoko, Kukuh Wisnuaji; Mahmud, Faizal; Billahi, Bagus Acung (Jurnal Pengabdian KOLABORATIF, 2026)
This community service activity aims to improve the technical and managerial competencies of construction workers in implementing drilled shaft (bored pile) foundations using a semi-mechanical drilling method. The activity was conducted at the BULOG warehouse construction project in Demak Regency, involving 30 workers from PT. Mitra Wardhana. The methods employed included training, demonstrations, direct on-site assistance, and evaluation through pre-test and post-test. The materials delivered covered the stages of drilled shaft construction, semi-mechanical drilling techniques, quality control, and the implementation of occupational health and safety (OHS). The results indicated an average increase of 29.7% in participants’ understanding, demonstrating the effectiveness of practice-based mentoring in enhancing workforce competence. In addition, the activity produced outputs in the form of Standard Operating Procedures (SOP) and technical documentation as sustainable work guidelines. Increased awareness of OHS was also observed through improved work behavior that is more disciplined and safety-oriented. Overall, this activity successfully addressed the partner’s problems and contributed to improving the quality of drilled shaft construction in a more effective, safe, and standardized manner.
Keywords: Community Service; Drilled Shaft Foundations; Semi-Mechanical Drilling; Quality Control; Occupational Health and Safety